Labor Instability in Peru and its Impacts on Psychology from a View of Psychoanalysis - Llique Ramírez, Rosa Natalí (2016)
The present article tries to offer a wide vision of the labor instability as a phenomenon that affects the Peruvian workers in all the labors regimens. Not only from the perspective of the labor law but from a psychological perspective for which the psychoanalytic concepts used by Sigmund Freud will join, as well as to show, from the point of view of the authors, that the labor instability is a phenomenon that concerns the health so much physical as psychological and emotional of the worker. Finally, the authors, try to offer ways to fight.